CERMIN SEBAGAI IDE PENCIPTAAN FOTOGRAFI FASHION PADA BAYI DENGAN BAJU RAJUT - Yustina Novita Sari; Edial Rusli; Adya Arsita (Institut Seni Indonesia Yogyakarta, 2021)
Mirror as The Idea of Fashion Photography Creation for Knitted Baby Clothes. Knit clothes are clothing made from yarn with a creative knitting process by linking the yarns so that they are formed into a clothing item with the variety of patterns and colors of the yarns that will show pattern on the clothes. Lack of promotion makes the fashion product just known by few people, especially the knitwear worn by babies aged 0 to 12 months. Therefore it is deemed necessary to draw up a marketing strategy in the form of a photo catalog. The creation of this photography work serves to help promote knitwear, especially for babies aged 0 to 12 months, to the general public. Fashion photography is a branch of photography focusing on the clothes, accessories, and other goods that will promote a product. In commercial photography, some creative processes of this creation used a light setting and some concepts that will strengthen the visual of the photo. The methods used were conducting stages of exploration, experimentation, and digital processing. Data research is done at the stage of exploration, along with market analysis, and SWOT analysis to strengthen the visual of the photography. The result shows that this fashion photography hopefully would give some visual insights and new references that could enrich the photography creation in portraying the knitted baby clothes worn by 0-12 months babies. Another result shows that the photoworks could be implemented in promotion media or knitwear product advertisements. ABSTRAKBaju rajut adalah baju yang terbuat dari benang dengan proses kreatif rajut yang cara pembuatannya mengaitkan benang secara teratur sehingga terbentuklah sebuah baju dengan corak dan warna benang yang beragam yang akan terbentuk di baju tersebut. Kurangnya promosi menyebabkan sedikit masyarakat yang mengetahui produk busana khususnya baju rajut yang dikenakan oleh bayi dengan usia 0 hingga 12 bulan. Oleh sebab itu, dianggap perlu untuk menyusun strategi pemasaran dalam bentuk foto katalog. Penciptaan karya ini bertujuan untuk membantu mempromosikan baju rajut, khususunya untuk bayi dengan usia 0-12 bulan, kepada khalayak umum. Fotografi fashion adalah cabang fotografi yang fokus pada busana, aksesoris, dan perlengkapannya yang berfungsi untuk mempromosikan sebuah produk. Dalam dunia fotografi komersial proses kreatif pembuatan karya menggunakan penataan cahaya dan konsep yang dapat memperkuat foto. Metode yang digunakan meliputi tahapan eksplorasi, eksperimentasi, dan proses olah digital. Dalam tahapan eksplorasi dilakukan pencarian data, analisis pasar, dan analisis SWOT untuk memperkuat penataan visual karya fotografi. Hasil penciptaan karya fotografi fashion ini diharapkan mampu memberi tampilan visual dan menjadi referensi baru yang bisa memperkaya penciptaan fotograf. Ide penciptaan karya dengan menggunakan cermin bertujuan untuk membentuk refleksi yang menjadi fokus utama dalam foto yang dapat menampilkan detail baju rajut.